Performance study on co-gasification of coal with sawdust and sawdust pellet in downdraft gasifier - Fatin Zafirah, Mansur (2020)
Gasification is a thermochemical conversion technology in which complex organic fuels are converted into syngas that are used to generate energy in the presence of limited oxygen supplied by steam or air. A decline in coal resources and environmental deterioration coupled with a high pre-processing cost and tar formation are usually associated with coal and biomass gasification. Thus, the co-gasification of biomass and coal is an alternative approach that facilitates a trade-off between renewable and nonrenewable resources. However, low energy density, high moisture content and different decomposition behaviours serve as technical barriers to co-gasification. This study aimed to compare raw biomass and pre-treated biomass co-gasified with coal to investigate pretreated biomass’s reliability in enhancing gasification performance. Sawdust (SD) and sawdust pellets (SDP) as well as the blends of these two feedstocks with sub-bituminous coal (CL) were investigated. Feedstock properties, like structural analysis, proximate analysis, ultimate analysis, higher heating value, chemical composition etc. were determined for CL, SD, and SDP and coal-biomass mixtures at different ratios (20%, 50% and 75%). Properties of the sawdust showed improvement as the feedstock was pelletized. Moreover, the thermogravimetric analysis (TGA) was performed in an air environment to study thermal behaviour and this study adopted the Kissinger, Flynn-Wall-Ozawa and Distribution Activation Energy Model methods to measure the kinetic analysis. Results show that lower activation energy (Ea) for CL/SD (103.82 ± 4.39 kJ/mol) and CL/SDP (88.79 ± 18.56 kJ/mol) was found at 75% coal ratio. There is also positive synergy for both CL/SD and CL/SDP employed by the three models. The addition of CL enhances the degradation of SD and SDP, increase the ΔEa, lower the Ea and indicates a reactive reaction. It was found that SD possessed a higher ΔEa than SDP, with an average difference of 14%, 23% and 38% at blending ratios of 75%, 50% and 25%, respectively. Furthermore, mixtures of CL with SD and SDP were gasified in a down-draft fixed bed gasifier to quantify the effect of coal ratio, gasification temperature and equivalence ratio of the air (ERair) on the gaseous concentration (H2, CO, CO2 and CH4), syngas higher heating value (HHVsyngas), syngas yield (Ysyngas), carbon conversion efficiency (ηCCE), cold gas efficiency (ηCGE) and solid-gas conversion efficiency (ηSGC). The parametric investigation as well as the optimum condition for maximizing H2 and CO were evaluated by adopting the Response Surface Methodology (RSM) method and sensitivity analysis using the ASPEN Plus model. Findings from both parametric approaches are similar, indicating that with an increase in gasification temperature, the production of gaseous composition, mainly the H2 and CO, also increases while enhancing the HHVsyngas, Ysyngas, ηCCE and ηCGE. Moreover, the highest content of H2, CO and CH4 is also associated with a lower ERair, thus, improving the HHVsyngas. Meanwhile, for the maximum production of CO2, Ysyngas and ηCCE, a higher ERair is favourable. It was found that the best conditions determined by RSM-CCD are much more specific than that indicated by the simulation model due to steady-state assumption in the simulation model and neglecting the heat and mass transfer inside the gasifiers. Instead, both the optimum parameters are within the range in which CL/SD favours a high coal ratio (75 %) and CL/SDP favours a lesser coal ratio (50-61 %) at a high gasification temperature and low ERair for the maximum production of H2 (12.30 -14.07 %), CO (14.63 -16.47 %) and HHVsyngas (5.74 to 6.66 MJ/kg). The RSM-CCD method resulted lesser percentage error (0.8-3.5%) than the simulation model (8.0-12.57%) when compared with the experimental study under the most conducive conditions. Therefore, co-gasified CL with SDP can potentially be a substitute for SD with the minimum amount of CL for similar gasification performances.